2017
DOI: 10.1128/aac.00155-17
|View full text |Cite
|
Sign up to set email alerts
|

Rifabutin Is Active against Mycobacterium abscessus Complex

Abstract: Lung infections caused by Mycobacterium abscessus are emerging as a global threat to individuals with cystic fibrosis and to other patient groups. Recent evidence for human-to-human transmission worsens the situation. M. abscessus is an intrinsically multidrug-resistant pathogen showing resistance to even standard antituberculosis drugs, such as rifampin. Here, our objective was to identify existing drugs that may be employed for the treatment of M. abscessus lung disease. A collection of more than 2,700 appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
167
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(184 citation statements)
references
References 63 publications
(110 reference statements)
16
167
0
Order By: Relevance
“…38 Cross-species gene transfer has helped to create multidrug-resistant strains, some even showing resistance to TB drugs such as rifampin. 39,40 In summary, by reporting the first medically relevant MtMetA and MaMetA crystal structures, we hope that new avenues of structure-based drug design will be open for developing targeted and effective therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…38 Cross-species gene transfer has helped to create multidrug-resistant strains, some even showing resistance to TB drugs such as rifampin. 39,40 In summary, by reporting the first medically relevant MtMetA and MaMetA crystal structures, we hope that new avenues of structure-based drug design will be open for developing targeted and effective therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Since it has recently been shown that rifabutin has a promising activity against M. abscessus (26,29), the second objective of our study was to compare the activity of tedizolid and rifabutin and to evaluate whether combinations comprising these two drugs have a potential therapeutic interest. In the macrophage, tedizolid and rifabutin were similarly active in improving the activity of imipenem alone (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Large studies have estimated that the prevalence of pulmonary NTM among CF patients is between 6–13% [3]. While acquisition of M. abscessus is typically attributed to contaminated water or soil, recent studies have demonstrated human-to-human transmission in patients with cystic fibrosis [46]. Two outbreaks of M. abscessus with genetically identical isolates were reported by Bryant et al in the United Kingdom amongst a CF population, raising concern for cross-infection [7].…”
Section: Nosocomial Ntm Respiratory Infection/colonizationmentioning
confidence: 99%
“…M. abscessus pulmonary infection is not considered curable unless surgical resection can be performed. Medical therapy is complex and typically includes parenteral agents such as Amikacin, Imipenem or Cefoxitin and macrolides [4]. Tigecycline, linezolid, and rarely fluoroquinolones may also be administered depending on available susceptibility patterns.…”
Section: Nosocomial Ntm Respiratory Infection/colonizationmentioning
confidence: 99%
See 1 more Smart Citation